New insights into heterogeneous generation and evolution processes of sulfate radicals for phenol degradation over one-dimensional a-MnO2 nanostructures - Wang, Yuxian; Indrawirawan, S.; Duan, X.; Sun, Hongqi; Ang, Ming; Tade, Moses; Wang, Shaobin (Elsevier BV, 2015)
Heterogeneous activation of peroxymonosulfate (PMS) has become an attractive approach for catalytic oxidation since it can not only provide sulfate radicals as an alternative to hydroxyl radicals, but also avoid the metal toxicity in homogeneous catalysis. In this study, three one-dimensional (1D) a-MnO2 nanostructures, nanorods, nanotubes and nanowires, were fabricated by a one-pot hydrothermal method without addition of any surfactants. Shape-dependent performance of 1D a-MnO2 was observed in catalytic degradation of phenol solutions. The phenol oxidation can be described by a first-order kinetic model and the activation energies of phenol oxidation on three a-MnO2 materials were estimated to be 20.3, 39.3 and 87.1 kJ/mol on nanowires, nanorods, and nanotubes, respectively. Both electron paramagnetic resonance (EPR) spectra and competitive radical tests were applied to investigate the PMS activation processes and to differentiate the major reactive species dominating the catalytic oxidation. The processes of PMS activation, evolution of sulfate radicals, and phenol degradation pathways were clearly illustrated.